Plasma Chemokines in Patients with Alcohol Use Disorders: Association of CCL11 (Eotaxin-1) with Psychiatric Comorbidity - García-Marchena, Nuria; Araos, Pedro Fernando; Barrios, Vicente; Sánchez-Marín, Laura; Chowen, Julie A.; Pedraz, María; Castilla-Ortega, Estela; Romero-Sanchiz, Pablo; Ponce, Guillermo; Gavito, Ana L.; Decara, Juan; Silva, Daniel; et al. (Frontiers in Psychiatry, 2017)
Recent studies have linked changes in peripheral chemokine concentrations to the presence of both addictive behaviors and psychiatric disorders. The present study further explore this link by analyzing the potential association of psychiatry comorbidity with alterations in the concentrations of circulating plasma chemokine in patients of both sexes diagnosed with alcohol use disorders (AUD). To this end, 85 abstinent subjects with AUD from an outpatient setting and 55 healthy subjects were evaluated for substance and mental disorders. Plasma samples were obtained to quantify chemokine concentrations [C-C motif (CC), C-X-C motif (CXC) and C-X3-C (CX3C) motif chemokines]. Abstinent AUD patients displayed a high prevalence of comorbid mental disorders (72%) and other substance use disorders (45%). Plasma concentrations of chemokines CXCL12/SDF-1 (p<0.001) and CX3CL1/fractalkine (p<0.05) were lower in AUD patients compared to controls, whereas CCL11/eotaxin-1 concentrations were strongly decreased in female AUD patients (p<0.001). In the alcohol group, CXCL8 concentrations were increased in patients with liver and pancreas diseases and there was a significant correlation to AST/GOT (r=+0.456, p<0.001) and GGT (r=+0.647, p<0.001). Focusing on comorbid psychiatric disorders, we distinguish between patients with additional mental disorders (N=61) and other substance use disorders (N=38). Only CCL11 concentrations were found to be altered in AUD patients diagnosed with mental disorders (p<0.01) with a strong main effect of sex. Thus, patients with mood disorders (N=42) and/or anxiety (N=16) had lower CCL11 concentrations than non-comorbid patients being more evident in women. The alcohol-induced alterations in circulating chemokines were also explored in preclinical models of alcohol use with male Wistar rats. Rats exposed to repeated ethanol (3 g/kg, gavage) had lower CXCL12 (p<0.01) concentrations and higher CCL11 concentrations (p<0.001) relative to vehicle-treated rats. Additionally, the increased CCL11 concentrations in rats exposed to ethanol were enhanced by the prior exposure to restraint stress (p<0.01). Concordantly, acute ethanol exposure induced changes in CXCL12, CX3CL1 and CCL11 in the same direction to repeated exposure. These results clearly indicate a contribution of specific chemokines to the phenotype of AUD and a strong effect of sex, revealing a link of CCL11 to alcohol and anxiety/stress.